Implementasi Metode Iqro’ Pada Anak Usia Dini Di Era Covid-19 - Siti Raihani Sholehah, Annisa Berliana Jaenudin, Hisny Fajrussalam, Ida Rahmawati, (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Early childhood is a golden age, where this is the right moment for educators to teach learning to read the Qur'an. The Covid-19 era is not an obstacle for PAUD institutions to implement learning to read the Qur'an, although of course there are some obstacles in its implementation. The purpose of this research activity is to describe how the implementation of the Iqro' method in learning to read the Qur'an in early childhood in the Covid-19 era. The method used in this research is descriptive qualitative method using interview, observation and documentation techniques. The results showed that the TK Labschool UPI Purwakarta implemented a private CBSA learning system, both when learning was carried out online through Zoom meetings and when it was carried out offline. The direct interaction between teachers and children makes the application of the Iqro method more effective when it is carried out offline. To monitor the child's progress, the teacher records it in the communication book. The attractiveness of the learning media used is a supporting factor in the application of the Iqro 'method. The inhibiting factor for the implementation of the Iqro' method is the attention of children who are easily distracted.